Epistemic and alethic modalities in online talk shows in Russian and English languages - Kastsiuchenka, Viktoryia Y. (Journal of the Belarusian State University. Philology, 2019)
Two cognitive modalities (epistemic and alethic) differ in the semantics and means of language expression. Epistemic modality is concentrated in the predicate, reflects the intellectual state of the speaker (subject) and is expressed by the verbs of thought, knowledge and assumption; the alethic modality is outside the syntactic structure of the utterance and is expressed by means of parenthetical (modal) words and phrases that give modal or emotional-modal assessment of what is said in the statement. On the material of 8 Russian and 8 English fragments of online talk shows (the fragment consists of 1000 words in each researched language) cognitive modal meanings were identified. Epistemic verbs appear in the following modal meanings: verbs of opinion, assumption; verbs of knowledge. Alethic modal meanings in terms of confidence/doubt can be divided into two groups: assertive and presumptive. The main similarities and differences in the lexical composition and use of these modal meanings between Russian and English talk shows were found, namely: the quantitative representation of the meanings of cognitive modality (epistemic and alethic together) is 1.8 times higher in English material than in Russian; in the class of epistemic modal meanings, English and Russian texts differ in the unit weight of verbs expressing confident knowledge, on the one hand, and the verbs of assumption, on the other hand: in Russian talk shows verbs of knowledge predominate (90 usages, which is 74 % of the number of all the usage of epistemic verbs), while in the English material the majority are verbs of opinion (105 usages, 58 %). Іn both languages the assertive modal meanings predominate in comparison with the presumptive ones, which indicates the speakerʼs desire to be convincing.